109k views
2 votes
Which of the following would give the correct binomial expansion for the expression below?

(x - 2)^4

User Nyegaard
by
5.9k points

2 Answers

5 votes
(x - 2)^4

= (x - 2)^4

= (x - 2) * (x - 2) * (x - 2) * (x - 2)

= x^4 - 8x^3 + 24x^2 - 32x + 16




Hope that helps!!!! (Answer: x^4 - 8x^3 + 24x^2 - 32x + 16, this is the answer if that's one of your choices, since I didn't see any.)?.
User Elmazzun
by
6.9k points
3 votes
4x-8=0
4(x-2)=0
x-2=0
X=2
User Jollymorphic
by
6.0k points